2011
DOI: 10.15208/pieb.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Motivating the Nigerian academic and non-academic staff for sustainable higher education: Insights for policy options

Abstract: The deteriorating economic environment over the last decade, due in part to declining commodity prices and oil price and exchange rate fluctuations, has shrunk national budgets. Simultaneously, high levels of demographic growth rates have swollen the ranks of the university-age population. Pressures to expand higher education at all levels persist. However, additional public resources for the sector are not likely to become available in the near future. A very critical challenge in an environment of rising dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…A synthesis of 25 studies on women in educational leadership and management in Zimbabwe (Moyo et al (2020), identified 'female ways of leading' as being characterized as collegial, collaborative and caring. Similarly, Nosike and Oguzor's (2011) examined the leadership styles of male and female principals in Nigeria. Principals, teachers, and students were all asked to discuss the styles of leadership commonly adopted by male and female principals and the data show that female principals adopt a democratic style of leadership to a greater extent than men.…”
Section: Leadership Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…A synthesis of 25 studies on women in educational leadership and management in Zimbabwe (Moyo et al (2020), identified 'female ways of leading' as being characterized as collegial, collaborative and caring. Similarly, Nosike and Oguzor's (2011) examined the leadership styles of male and female principals in Nigeria. Principals, teachers, and students were all asked to discuss the styles of leadership commonly adopted by male and female principals and the data show that female principals adopt a democratic style of leadership to a greater extent than men.…”
Section: Leadership Stylesmentioning
confidence: 99%
“…shows that women's leadership is more collegial, collaborative and caring than that of men. Nosike and Oguzor (2011) report that Nigerian women principals exercise more democratic styles, a view supported by Aladejana and Aladanje (2005), who state that Nigerian schools headed by women are 'better managed'. This evidence suggests that women not only have to be determined and resilient to access leadership but may also offer an approach that is more engaging of staff and stakeholders, to work towards school improvement.…”
Section: Leadership Stylesmentioning
confidence: 99%